1975
DOI: 10.1021/jm00240a027
|View full text |Cite
|
Sign up to set email alerts
|

3-Substituted 2-formylquinoxaline 1,4-dioxides

Abstract: The methylnitrone of 3-methyl-1,4-dioxidoquinoxaline-2-carboxaldehyde (1) has been exceptional antibacterial activity in vivo. Derivatives of 3-hydroxymethyl-1,4-dioxidoquinoxaline-2-carboxaldehyde and 3-acetoxymethyl-1,4-dioxidoquinoxaline-2-carboxaldehyde were prepared. Several of these compounds were found to be antibacterial agents of the same order of activity as I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1975
1975
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 3 publications
(3 reference statements)
0
7
0
Order By: Relevance
“…These authors proved that a metabolic bioactivation in the sheep of 2,3-dimethylquinoxaline 1,4-dioxides take place to afford the more active 2-hydroxymethyl-3-methylquinoxaline 1,4-dioxide. On the other hand subsequent studies of Edwards et al reported that 3-hydroxymethyl-1,4-dioxidoquinoxaline-2-carboxaldehyde and 3-acetoxymethyl-1,4-dioxidoquinoxaline-2-carboxaldehyde derivatives were in vivo active at the same order of activity of methylnitrone derivative [85]. The activity of nitrone derivatives was also studied by Bambury et al [86][87].…”
Section: Mutagenic Properties Of the Growth-promoting Quin Olaq Carmentioning
confidence: 93%
“…These authors proved that a metabolic bioactivation in the sheep of 2,3-dimethylquinoxaline 1,4-dioxides take place to afford the more active 2-hydroxymethyl-3-methylquinoxaline 1,4-dioxide. On the other hand subsequent studies of Edwards et al reported that 3-hydroxymethyl-1,4-dioxidoquinoxaline-2-carboxaldehyde and 3-acetoxymethyl-1,4-dioxidoquinoxaline-2-carboxaldehyde derivatives were in vivo active at the same order of activity of methylnitrone derivative [85]. The activity of nitrone derivatives was also studied by Bambury et al [86][87].…”
Section: Mutagenic Properties Of the Growth-promoting Quin Olaq Carmentioning
confidence: 93%
“…For the synthetic preparation, see: Haddadin & Issidorides (1965); Issidorides & Haddadin (1966). For background to quinoxaline di-N-oxide compounds, see: Edwards et al (1975) and for their biological activity, see: Urquiola et al (2008). For a related structure, see: Wang et al (2010).…”
Section: Related Literaturementioning
confidence: 99%
“…Quinoxaline di-N-oxide compounds are widely used in sterilization and growth-promoting of animals, pharmacological properties usable as intermediates for producing plant protection agents (Edwards et al,1975). There has been a growing interest in the syntheses of quinoxaline di-N-oxide compounds that have both biological and commercial importance (Urquiola et al, 2008).…”
Section: S1 Commentmentioning
confidence: 99%
“…97 The high in vivo activity of 2,3-dimethyl- In addition to their use as feed additive^,^^"^ quinoxaline 1,4-dioXides have been patented for the treatment of diseases in aquatic animals'03 and as fungicides and herbicide^.^,^'^ There is also a report of the prophylactic effect of 6-chloro-2,3-dimethylquinoxaline 1,4-dioxide and 2,3-dimethylquinoxaline 1,4-dioxide on radiation injuries in mice.lo5 Tables TABLE 1. It has been shown that its in vitro activity is enhanced 10 to 100-fold under anaerobic conditions.…”
Section: Usesmentioning
confidence: 99%